(3LGeY GdYdhe hGdMces - (3YHO GdQMef Hf CMeO Hf QLH GdMfHdj GdqSdGej GdHZOGOj Ke GdOeTbqj, CHh GdaQL, Rjf GdOjf,J (B795 (3g` s ((3CMeO Hf eMe(B\(3O Hf CMeO Gdecj GdUYjOj GdMfHdj s)
(3ChdgG (B:s
(3bGd GdTjN GdMeO ddg GdPj Gced dfG GdOjf hCJe YdjfG GdfYeI hLYd GeJfG hddg GdMeO NjQ CeI CeG HYO aEf Gddg JYGdj HYK eMeOkG Udj Gddg Ydjg hSde HLhGQ eY Gdcde hNUI HHOGFg GdMce s
(3BNQgG (B:s
(3haj GdeSfO Yf Hf eSYhO QVi Gddg Yfg bGd Cf QShd Gddg Udj Gddg Ydjg hSde Yde ahGJM GdNjQ hLhGeYg hLhGeY GdNjQ hahGJMI hNhGJeI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B118s
(3eUOQ GbJfGA GdCUd (B:s
(3JQcjG (B(330) s
Keywords: (3eJaQbGJs